Structures and reactivity of peroxy radicals and dimeric products revealed by online tandem mass spectrometry - Tomaz, Sophie (Nat Commun, 2021)
Organic peroxy radicals (RO(2)) play a pivotal role in the degradation of hydrocarbons. The autoxidation of atmospheric RO(2) radicals produces highly oxygenated organic molecules (HOMs), including low-volatility ROOR dimers formed by bimolecular RO(2) + RO(2) reactions. HOMs can initiate and greatly contribute to the formation and growth of atmospheric particles. As a result, HOMs have far-reaching health and climate implications. Nevertheless, the structures and formation mechanism of RO(2) radicals and HOMs remain elusive. Here, we present the in-situ characterization of RO(2) and dimer structure in the gas-phase, using online tandem mass spectrometry analyses. In this study, we constrain the structures and formation pathway of several HOM-RO(2) radicals and dimers produced from monoterpene ozonolysis, a prominent atmospheric oxidation process. In addition to providing insights into atmospheric HOM chemistry, this study debuts online tandem MS analyses as a unique approach for the chemical characterization of reactive compounds, e.g., organic radicals.